2023
DOI: 10.1088/2516-1091/acac57
|View full text |Cite
|
Sign up to set email alerts
|

Active upper limb prostheses: a review on current state and upcoming breakthroughs

Abstract: The journey of a prosthetic user is characterized by the opportunities and the limitations of a device that should enable activities of daily living (ADL). In particular, experiencing a bionic hand as a functional (and, advantageously, embodied) limb constitutes the premise for promoting the practice in using the device, mitigating the risk of its abandonment. In order to achieve such a result, different aspects need to be considered for making the artificial limb an effective solution to accomplish activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 319 publications
(309 reference statements)
0
16
0
Order By: Relevance
“…The primary hurdle in achieving optimal patient–neuroprosthetic interface thus far is not solely hardware or software-related, but also centers on the signal quality. 6 The RPNI not only represents a clinical milestone by leveraging the inherent regenerative properties of transected peripheral nerves to reinnervate end organ targets for improved motor signal quality and sensory feedback, but it also introduces a pioneering engineering platform. This platform has the potential to incorporate cutting-edge engineering techniques to develop neuroprosthetic devices that can seamlessly integrate with humans, including ultraflexible, smart implants to interface with the muscle graft RPNIs, 61 advanced algorithms for data processing and decoding, 62 biomimetic encoding strategies that facilitate neuron-like sensory signaling, 32 57 and dexterous robotic devices that execute precise motor commands with multiple DoFs.…”
Section: Regenerative Peripheral Nerve Interface Toward Neurobionicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary hurdle in achieving optimal patient–neuroprosthetic interface thus far is not solely hardware or software-related, but also centers on the signal quality. 6 The RPNI not only represents a clinical milestone by leveraging the inherent regenerative properties of transected peripheral nerves to reinnervate end organ targets for improved motor signal quality and sensory feedback, but it also introduces a pioneering engineering platform. This platform has the potential to incorporate cutting-edge engineering techniques to develop neuroprosthetic devices that can seamlessly integrate with humans, including ultraflexible, smart implants to interface with the muscle graft RPNIs, 61 advanced algorithms for data processing and decoding, 62 biomimetic encoding strategies that facilitate neuron-like sensory signaling, 32 57 and dexterous robotic devices that execute precise motor commands with multiple DoFs.…”
Section: Regenerative Peripheral Nerve Interface Toward Neurobionicsmentioning
confidence: 99%
“…1). 6 State-of-the-art research in neuroprosthesis development aims to improve integration into the human body and has shown promise in recent clinical trials. [7][8][9][10] In the past decade, many research groups have developed functional neuroprosthetic interfaces that enable motor control using brain signals, such as electrocorticogram 11,12 and electroencephalogram, 13,14 as well as surface electromyography (EMG) signals.…”
mentioning
confidence: 99%
“…Previous experiments have shown that tree-based models such as Random Forests seem to perform well in a supervised multimodal HMI for activity recognition [24]. Additional factors such as a co-adaptive environment can further enhance HMI performance [30,31]. Hereby, human and machine interact through closed feedback loops in a mutual learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, muscle synergy theory has been already adapted as a framework for proportional myoelectric control [23]. In this context, synergy computation results in the dimensionality reduction of many input EMG signals, by obtaining few time-varying continuous signals used to control the actuators of a robotic prosthesis [24]. However, such an approach implies that each synergy must represent one of the two rotational directions (clockwise and anti-clockwise) of a DC electric motor actuating a single degree of freedom (DoF) [23].…”
Section: Introductionmentioning
confidence: 99%